The impact mechanism of carbon emission reduction performance on financial performance based on carbon neutral targets: Evidence from Chinese energy enterprises - Sokolov, Boris Ivanovich; Jiang, Xuyan; Ding, Xiaowei (Nurture, 2024)
Purpose: Low-carbon and green technologies are crucial for achieving industrial structure upgrades and significant leaps forward in the development of energy enterprises. Therefore, this paper examines the correlation between carbon emission reduction and financial performance in energy firms. Design/Methodology/Approach: A two-way fixed-effects model is developed using data from 33 Chinese energy-listed companies between 2015 and 2020. Findings: The benchmark regression results show that improving a company's carbon emission reduction performance leads to better financial performance. Moreover, assuming corporate responsibility for reducing emissions can boost companies' reputations and foster better relationships with stakeholders. The trustworthiness of the standard regression outcome is validated through alternative independent variables, reducing time frames, and incorporating previously omitted factors. The results of heterogeneity analyses show that reducing carbon emissions has the same effect on financial performance across all regional characteristics and equity subgroups. Furthermore, the internal transmission mechanism analysis reveals that female leadership positively moderates the effect, while financing constraints negatively moderate the relationship between carbon emission reduction performance and financial performance. Conclusion: Under the national green development strategy of achieving carbon neutrality and carbon peaking, the carbon information disclosure system should be improved by the government; enterprises should implement innovative methods for low-carbon economic management and operation; and regulators should establish effective green regulations, incentives, and constraints. This paper offers a comprehensive guide for energy companies and their stakeholders to reduce carbon emissions, thereby achieving sustainability.